(untitled) (Uzbek Scholar Journal, 2023)
As we all know, tourism is closely related to regions. The main element of the tourist system is the area that attracts the tourist, the place where he makes his trip and spends some time - the goal, that is, the destination. The concept of "destination" comes from the Latin word "location" and has been one of the main terms of the conceptual apparatus of foreign researchers and tourism practitioners for about 30 years. Despite its widespread use, the concept of "destination" itself has not become an object of separate analysis in tourism literature. However, both from the point of view of science and from the point of view of effective management, it is fundamentally important to analyze the essence, structure and content of the concept of "destination". Below, we will dwell a little on the definitions given to the concept of "destination" by the most famous and influential foreign researchers of tourism.